Remarkable : a novel - Foley, Lizzie K. (Dial Books for Young Readers, 2012)
Ten-year-old Jane Doe, the only student average enough to be excluded from the town of Remarkable's School for the Remarkably Gifted, is joined at her public school by the trouble-making Grimlet twins, who lead her on a series of adventures involving an out-of-control science fair project, a pirate captain on the run from a mutinous crew, a lonely dentist, and a newly constructed bell tower that endangers Remarkable's most beloved inhabitant--a skittish lake monster named Lucky.